Safety considerations of semaglutide in the potential treatment of Alzheimer's disease: A pooled analysis of semaglutide in adults aged ≥ 65 years - Marwan Sabbagh; Cristina Boschini; Sharon Cohen; Magnus Fugger; Frank Jessen; Sune Dandanell; Sue D. Pedersen; Luis Rafael Solís Tarazona; Vanita R. Aroda (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2025)
Abstract INTRODUCTION The evoke/evoke+ trials are investigating semaglutide in a population with early Alzheimer's disease (AD). Specific analyses of semaglutide safety data in older adults are limited; therefore, in the current analysis, we aimed to evaluate safety considerations with semaglutide in adults ≥ 65 years. METHODS Adverse event (AE) data from three semaglutide phase 3a programs in participants ≥ 65 years with type 2 diabetes and/or overweight/obesity were pooled. Change in body weight was also assessed in a smaller subset of participants ≥ 65 years. RESULTS The analysis included 3529 participants ≥ 65 years. Baseline mean age and body mass index in participants ≥ 65 years were 69.3 to 70.2 years and 29.7 to 35.4 kg/m2, respectively, compared to 47.8 to 58.5 years and 31.3 to 36.7 kg/m2 in the overall population. AEs with semaglutide occurred in 73.6% to 92.4% of participants ≥ 65 years versus 73.2% to 90.8% of the overall population. AEs with semaglutide leading to permanent discontinuation appeared to be more frequent in participants ≥ 65 years (9.3%–12.4%) versus the overall population (5.7%–8.7%). Gastrointestinal disorders were the most frequently reported AEs with semaglutide in participants ≥ 65 years (44.6%–73.8%) and in the overall population (39.1%–73.4%). Participants aged ≥ 65 years receiving semaglutide had an estimated weight loss of 3.8% at week 52 compared to 0.1% with placebo. DISCUSSION Age ≥ 65 years did not appear to affect the safety considerations of semaglutide. The ongoing evoke/evoke+ trials will elucidate the balance of efficacy and safety in the treatment of early AD with semaglutide. Highlights This was a post hoc analysis evaluating adverse event (AE) data of semaglutide in people ≥ 65 years. The most common AE with semaglutide was gastrointestinal (GI). GI event rates were similar in people ≥ 65 years and the overall study populations.